Snorkel-biochar coupling enhances organic matter and nitrogen pollutant removal while mitigating greenhouse gas emissions through spatial redox regulation in bioretention systems - Ruohan Li; Wenying Sun; Yuepeng Deng; Hengxin Liu; Mingyue Yang; Yueming Han; Lixun Zhang (Water Research, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Mg/Fe-layered double hydroxide-loaded biochar enhances nitrogen retention and reduces geochemically reactive metal concentrations in paddy soil: Bacterial community responses - Hengxin Liu; Ruohan Li; Yueming Han; Yuntao Guan; Lixun Zhang (Process Safety and Environmental Protection, 2026)

A progressive physics-informed neural network method for porosity evaluation: a case study of the Qiongzhusi Formation shale - Pan Zhang; Benqi Zhang; Ruohan Shi; Zilong Ren; Yanghu Li; Weibiao Xie (Journal of Applied Geophysics, 2026)

Emulsion gels stabilized by millet chaff prolamin–gallic acid or –sucralose conjugates: characterization, application in curcumin, and mechanism insights - Yan Li; Jie Liu; Hao Wang; Biao Ma; Zihao Zhang; Ling Dang; Yajun Zheng; Ruohan Liu; Yi Li (Food Chemistry, 2026)

GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Toxoplasma gondii infection reduces CD59 expression through downregulation of JAK2/STAT3 signaling axis to enhance decidual NK cell cytotoxicity via the RAS/MAPK pathway - Shuyan Wang; Luyun Huo; Yan Zou; Ruohan Yang; Xiao Wang; Haixia Zhang; Liqin Ren; Jing Yang; Jie Li; Xuemei Hu; Yushan Ren (Inflammation Research, 2026)

Co-mitigating tire wear particles and their leachates across the life cycle: A critical review - Kejun Liao; Junyi Yu; Ruohan Huang; Wenjing Zhou; Yuwei Zhou; Junru Guo; Shengman Zhang; Chen Cai; Kaiming Peng; Xiangfeng Huang; Jia Liu (Water Research, 2026)

HOPO-functionalized MXene self-supporting membrane for highly efficient and selective uranium extraction from radioactive wastewater - Jiaxin Li; Yinlu Dong; Yu Wang; Xiangcao Chang; Jicui Wen; Yuhang Zhang; Wenhua Zhu; Lichan Xiao; Ruohan Guo; Chaoran Li; Zhiyun Meng; Ruolan Gu; et al. (Chemical Engineering Journal, 2026)

Host genotype-enriched rhizosphere microbes enhance pea (Pisum sativum L.) yield - Qinwen Yang; Qiong Liu; Ke Dong; Kaile Zhang; Chuanfa Wu; Ruohan Yin; Linying Xu; Zhijuan Feng; Tao Yang; Tida Ge (Plant and Soil, 2026)

Chemical reaction kinetics regulated dual-signal sensing system for discriminating EV-A71 and CV-A16 - Tongtong Ye; Wenjing Xu; Ruohan Tang; Yuhan Wang; Yang Li; Xuming Zhao; Hui Zhang; Lihua Chen (Analytica Chimica Acta, 2026)

Analysis of spatial heterogeneity and influencing factors of carbon emission efficiency at the provincial level in China based on machine learning - Xinglan Dai; Ruohan Zhang; Zishuai Zu; Ying Wang (Journal of Environmental Management, 2026)

Rambutan-inspired tri-layer architecture with regulated strain and lithium transport for high-capacity and stable lithium storage - Huan Du; Ganggang Ma; Ziqing Yin; Shaoqing Rao; Sheng Lin; Tianyi Zhang; Jingke Ren; Yucai Wu; Wei Zhang; Ruohan Yu; Dongyuan Zhao; Wei Li; et al. (Science Bulletin, 2026)

Co-exposure to multiple fine particulate matter constituents and adults obstructive sleep apnoea (OSA) in Southern China - Suhan Wang; Gongbo Chen; Peipei Dong; Hailin Xiong; Yuewei Liu; Ruohan Zhou; Ranxu Zhang; Qiong Ou (Environmental Pollution, 2026)

Wind-driven variability in phytoplankton dynamics in a semi-enclosed sea - Ruohan Sun; Xinyi Kang; Zhen Wang; Haibo Zhang; Hang Yin (Estuarine, Coastal and Shelf Science, 2026)

Facile synthesis of palladium nanoparticles loaded on zirconia/porous carbon nanocomposites via a ternary synergistic strategy for ultrasensitive adrenaline detection - Rou Wang; Lin Hao; Ruohan Yang; Hongyuan Yan; Penglian Ma; Yufan Zhang (Analytica Chimica Acta, 2026)

Identification of disease-associated gene expression signatures for mechanistic insights and drug prediction in dilated cardiomyopathy-induced heart failure - Wei Yu; Shuai Xu; Xin Tan; Hangyao Zhang; Ruohan Ma; Yiyao Zeng; Anchen Xu; Honghui Tang; Qin Rui; Yahui Song; Yafeng Zhou (Molecular and Cellular Biochemistry, 2026)

A small technology for big health: Blocking the potential spread of antibiotic resistomes from home composting of food waste by mature compost - Ruohan Xia; Lanxia Zhang; Guoxue Li; Wenhai Luo; Zhicheng Xu (Waste Management, 2026)

Levels and associated potential ecological risks of heavy metals in surface sediments from wetlands in the western Yellow River Delta - Ruohan Zhang; Zaiwang Zhang; Junxia Yang; Xu Zhang; Shanshan Liu; Jianchao Jin; Guangwu Liu; Changqing Shan; Jian Li; Jianhui Tang (Regional Studies in Marine Science, 2026)

Gallic acid-reinforced Rana chensinensis ovum protein isolates-Gellan gum thermally reversible emulsion gel: Insight of the structure and potential applications in dysphagia management - Ruixue Liu; Min Gao; Li Zhang; Shihan Wang; Ying Yang; Jing Bai; Ruohan Wang; Yongsheng Wang; Zhihan Wang (Food Research International, 2025)

Surface nitridation of Si enabled gradient artificial solid electrolyte interface and self-optimized structural evolution - Zhenyi Huang; Ruohan Yu; Jinshuai Liu; Yuxia Zhong; Lei Zhang; Liang Zhou (Science Bulletin, 2025)

Freeze–thaw impacts on the mechanical behavior of silty clay: Insights from experimental and DEM investigation - Run Liu; Rui Zhang; Ruohan Sun (Bulletin of Engineering Geology and the Environment, 2025)

One-step molding to prepare durable dual superlyophobic composites for non-loss mass transfer, immiscible solvent separation, and CO2 bubble removal - Chang-Lian Xu; Xingyue Wu; Yuqing Song; Jialin Liu; Ruohan Xiong; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Xin Qi; Guochun Lv; et al. (Journal of Environmental Chemical Engineering, 2025)

Carboxylesterase 1 regulates peroxisome proliferator-activated receptor gamma to inhibit the growth and metastasis of breast cancer cells - Jingli Wen; Lei Geng; Ruohan Wang; Xiaolei Zhang; Yanmin Sui; Xiaofang Liu; Xin Han (Journal of Molecular Histology, 2025)

Accurate identification and formation mechanism unraveling of radicals in UV-induced peracetic acid activation system using in-situ electron paramagnetic resonance - Long Chen; Ruohan Zhang; Zhaoli Liu; Fan Li; Boyu Huang; Wen Liu (Science Bulletin, 2025)

Integrative N-glycomics and N-glycoproteomics landscape reveals up-regulation of complex-type N-glycosylation in the tolerance of peach fruit to chilling injury - Huiwen Wang; Tonghao Cui; Jiaqi Wang; Ruohan Ou; Yilong Liu; Bo Zhang; Changjie Xu; Changqing Zhu; Miaojin Chen; Yanna Shi; Yuanjiang Pan; Kunsong Chen; et al. (Postharvest Biology and Technology, 2025)

Wood utilization and paleo-vegetation revealed by wooden remains excavated from ancient Dahe City site (AD 618–907) in Barkol, Xinjiang, northwest China - Ruohan Wang; Guilin Zhang; Yongqiang Wang; Biao Pan; Guolei Dun; Youcheng Xu; Hongen Jiang (Quaternary International, 2025)

Does land management scale influence farmers' utilization of straw resources? Empirical evidence from rural China - Jialan Zhang; Ruohan Zhang; Kuan Zhang; Dingde Xu; Yanbin Qi; Xin Deng (Environmental Impact Assessment Review, 2025)

Temporomandibular joint CBCT image segmentation via multi-view ensemble learning network - Piaolin Hu; Jupeng Li; Ruohan Ma; Kai Zhang; Yong Guo; Gang Li (Medical & Biological Engineering & Computing, 2025)

Corrigendum to “Distribution characteristics, risk assessment, and quantitative source apportionment of typical contaminants (HMs, N, P, and TOC) in river sediment under rapid urbanization: A study case of Shenzhen river, Pearl River Delta, China” [Process Saf. Environ. Prot. 162 (2022) 155–168] - Ying Zhang; Wei Mao; Ruohan Li; Yang Liu; Peng Wang; Zelin Zheng; Yuntao Guan (Process Safety and Environmental Protection, 2025)

Paper strips-based narrowing colorimetry: An all-in-one strategy for rapid visual detection and adulteration identification of food dyes - Shuangshou Wang; Haiyang Li; Tong Li; Ruohan Xu; Chunyan Yang; Tianyou Geng; Tingxuan Yan; Qi Zhang; Daojin Li; Jingchong Yan; Yanshang Kang; Caibo Yue (Food Control, 2025)

Lab on a single microbead: An enzyme-free strategy for the sensitive detection of microRNA via efficient localized catalytic hairpin assembly - Yan Qi; Jiangtao Yu; Ming Lou; Yameng Yu; Ruohan Li; Zhenhao Zhang; Yuxuan Dai; Kejing Lao; Meng Cao; Xingchun Gou (Analytica Chimica Acta, 2025)

Generation of advanced glycation end products from glycated protein or fructose/glyoxal-protein adducts under in vitro simulated gastrointestinal digestion - Xiaojin Yuan; Shuqing Feng; Jianuo Li; Ruixin Guo; Chenxi Nie; Ruohan Zhai; Aobai Tu; Xinyu Cao; Min Zhang; Juxiu Li (Food Chemistry, 2025)

Joint probabilistic risk of organic micropollutants in the aquaculture seawater around Liaodong Peninsula - Yongle Zhu; Ruohan Zhang; Huaijun Xie; Lingyun Mo; Jingwen Chen; Kiwao Kadokami; Xuehua Li (Science of The Total Environment, 2024)

Inhibitory effects of potassium sorbate and ZnO nanoparticles on Escherichia coli and Staphylococcus aureus in milk-based beverage - Yuanyuan Zhang; Qianqian Yang; Feng Lu; Xiaoyang Wang; Ruohan Liang; Xiaodan Pu; Jianlei Chen; Dahai Zhang; Zhixiang Chen; Xuzhi Zhang (International Dairy Journal, 2024)

The impact of cryosphere service change on the social-ecological systems resilience: Evidence from the Qilian Mountains Area in China - Di Zhao; Jia Chen; Xiaowen Zhang; Ruohan Shi; Yang Xiao; Ziyan Chen (Journal of Environmental Management, 2024)

The Insular Cortex: An Interface Between Sensation, Emotion and Cognition - Ruohan Zhang; Hanfei Deng; Xiong Xiao (Neuroscience Bulletin, 2024)

Hyaluronic acid modulates gut microbiota and metabolites relieving inflammation: A molecular weight-dependent study - Chuan Zhang; Botao Wang; Leilei Yu; Ruohan Zhao; Qingsong Zhang; Chengcheng Zhang; Shumao Cui; Jianxin Zhao; Arjan Narbad; Wei Chen; Fengwei Tian; Qixiao Zhai (Science Bulletin, 2024)

Photoexcitation-induced efficient detoxification and removal of arsenite in contaminated water by a layered double hydroxide-supported polyacrylate stabilized ferrous sulfide composite - Wei Mao; Yibing Li; Lixun Zhang; Xuewu Shen; Yang Liu; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2024)

Covalent organic framework with donor-acceptor structure for rapid and sensitive photothermal sensing detection - Zhen Zhang; Zhenkai Hao; Ruohan Yang; Ruiping Shan; Xiangyang Li; Hongyan Zhang (Food Chemistry, 2024)

Research on precise phenotype identification and growth prediction of lettuce based on deep learning - Haiye Yu; Mo Dong; Ruohan Zhao; Lei Zhang; Yuanyuan Sui (Environmental Research, 2024)

Selective activations and functional connectivities to the sight of faces, scenes, body parts and tools in visual and non-visual cortical regions leading to the human hippocampus - Edmund T. Rolls; Jianfeng Feng; Ruohan Zhang (Brain Structure and Function, 2024)
Connectivity maps are now available for the 360 cortical regions in the Human Connectome Project Multimodal Parcellation atlas. Here we add function to these maps by measuring selective fMRI activations and functional connectivity increases to stationary visual stimuli of faces, scenes, body parts and tools from 956 HCP participants. Faces activate regions in the ventrolateral visual cortical stream (FFC), in the superior temporal sulcus (STS) visual stream for face and head motion; and inferior parietal visual (PGi) and somatosensory (PF) regions. Scenes activate ventromedial visual stream VMV and PHA regions in the parahippocampal scene area; medial (7m) and lateral parietal (PGp) regions; and the reward-related medial orbitofrontal cortex. Body parts activate the inferior temporal cortex object regions (TE1p, TE2p); but also visual motion regions (MT, MST, FST); and the inferior parietal visual (PGi, PGs) and somatosensory (PF) regions; and the unpleasant-related lateral orbitofrontal cortex. Tools activate an intermediate ventral stream area (VMV3, VVC, PHA3); visual motion regions (FST); somatosensory (1, 2); and auditory (A4, A5) cortical regions. The findings add function to cortical connectivity maps; and show how stationary visual stimuli activate other cortical regions related to their associations, including visual motion, somatosensory, auditory, semantic, and orbitofrontal cortex value-related, regions.

Bacteriostatic mechanism of Lactiplantibacillus plantarum CS3 cell-free supernatant of on soy sauce spoilage bacteria - Shuyu Zhang; Ruohan Yao; Qifeng Wang; Wenjun Wang; Shuoshuo Zhao; Hao Wang; Ling Zhu; Yunping Yao; Guozhong Zhao (Food Bioscience, 2024)

Shaking table tests on deformation pattern and failure mechanism of fault-crossing tunnels in non-rupture scenario - Ruohan Li; Xu Zhao; Emilio Bilotta; Jinghua Zhang; Mi Zhao; Jingqi Huang; Yong Yuan (Soil Dynamics and Earthquake Engineering, 2024)

Overexpression of MrMYB12 or MrMYB12/MrF3’5’H results in flavonol-rich tomato fruit that improves resistance against Botrytis cinerea during the shelf life period - Yunlin Cao; Ruining Zhang; Ruohan Ou; Yuyang Mei; Xiangrui Cui; Tong Zhang; Xiaochun Yang; Yanna Shi; Xiaoyong Zhao; Changjie Xu; Kunsong Chen; Xian Li (Postharvest Biology and Technology, 2024)

One-step process for debromination and mineralization of tetrabromobisphenol a by a layered double oxide-supported sulfurized nanoscale zero-valent iron under ambient conditions - Ruohan Li; Lixun Zhang; Ying Zhang; Zhengfang Zhang; Yuntao Guan (Chemical Engineering Journal, 2024)

Morphological and physiological plasticity of Catalpa bungei roots under partial root-zone drought as affected by nitrogen forms - Tiantian Sun; Ruohan Ren; Mingming Xing; Qiuxiao Duan; Lang Zhao; Wenwen Yan; Yang Fang; Senyan Zhang; Hao Dong; Mengran Wang; Qimeng Heng; Wenyi Chen; et al. (New Forests, 2024)

Effects of tree density variations on outdoor heritage conservation: Numerical study of an ancient brick city wall with four orientations - Ting Zhang; Changchang Xia; Yan Ma; Ruohan Zhang; Shuai Han; Zhenyi Kong; Shuichi Hokoi; Yonghui Li (Building and Environment, 2024)

A DEM-based approach for modeling the thermal-mechanical behavior of frozen soil - Ruohan Sun; Run Liu; Huan Zhang; Rui Zhang; Yu Jiang; Ruilong Yin (European Journal of Environmental and Civil Engineering, 2024)

Unveil the potential in hydrogen activation and spillover towards NiMoS by Ni3S2 - A theoretical study - Xiaodong Liu; Hangyu He; Lijun Hu; Xiaohui Zhang; Ruohan Wang; Xuemin Yan (Fuel, 2024)

Characterization of carbonaceous particles by single particle aerosol mass spectrometer in the urban area of Chengdu, China - Junke Zhang; Rui Wang; Chunying Chen; Yunfei Su; Luyao Chen; Wei Zhang; Yingwei Xi; Yangchun Yu; Ruiyan Pu; Minghui Lu; Ruohan Wu; Xuhui Shen (Environmental Science and Pollution Research, 2024)

Identification of novel umami peptides from yeast extract and the mechanism against T1R1/T1R3 - Hao Wang; Wenjun Wang; Shuyu Zhang; Zhenhao Hu; Ruohan Yao; Hadiatullah Hadiatullah; Pei Li; Guozhong Zhao (Food Chemistry, 2023)

Adsorption and photocatalytic degradation of quinolone antibiotics from wastewater using functionalized biochar - Ning Cheng; Bing Wang; Miao Chen; Qianwei Feng; Xueyang Zhang; Shengsen Wang; Ruohan Zhao; Tao Jiang (Environmental Pollution, 2023)

Different cortical connectivities in human females and males relate to differences in strength and body composition, reward and emotional systems, and memory - Ruohan Zhang; Edmund T. Rolls; Wei Cheng; Jianfeng Feng (Brain Structure and Function, 2023)
Sex differences in human brain structure and function are important, partly because they are likely to be relevant to the male–female differences in behavior and in mental health. To analyse sex differences in cortical function, functional connectivity was measured in 36,531 participants (53% female) in the UK Biobank (mean age 69) using the Human Connectome Project multimodal parcellation atlas with 360 well-specified cortical regions. Most of the functional connectivities were lower in females (Bonferroni corrected), with the mean Cohen’s d = − 0.18. Removing these as covariates reduced the difference of functional connectivities for females—males from d = − 0.18 to − 0.06. The lower functional connectivities in females were especially of somatosensory/premotor regions including the insula, opercular cortex, paracentral lobule and mid-cingulate cortex, and were correlated with lower maximum workload ( r = 0.17), and with higher whole body fat mass ( r = − 0.17). But some functional connectivities were higher in females, involving especially the ventromedial prefrontal cortex and posterior cingulate cortex, and these were correlated with higher liking for some rewards such as sweet foods, higher happiness/subjective well-being, and with better memory-related functions. The main findings were replicated in 1000 individuals (532 females, mean age 29) from the Human Connectome Project. This investigation shows the cortical systems with different functional connectivity between females and males, and also provides for the first time a foundation for understanding the implications for behavior of these differences between females and males.

Calcium alginate-nZVI-biochar for removal of Pb/Zn/Cd in water: Insights into governing mechanisms and performance - Ruohan Zhao; Bing Wang; Pan Wu; Qianwei Feng; Miao Chen; Xueyang Zhang; Shengsen Wang (Science of The Total Environment, 2023)

High dimethylsulfoniopropionate concentrations in the surface seawater over the marginal seas of China and the Northwest Pacific Ocean during May–July of 2021 following La Niña - Lingxiao Li; Zhengguo Cui; Keming Qu; Hongsheng Wang; Ruohan Song; Xiaoke Hu; Shenghui Zhang; Tao Jiang; Mingying Zhou; Qingjing Hu (Marine Pollution Bulletin, 2023)

Blending loss-control and normal urea maximizes nitrogen utilization of summer maize by mitigating ammonia volatilization and nitrate leaching - Wenxuan Shi; Qian Zhang; Ruohan Xie; Kai Sheng; Jinfang Tan; Yilun Wang (Plant and Soil, 2023)

DEM investigation of the mechanical behavior of frozen soil along various stress paths - Ruohan Sun; Run Liu; Huan Zhang; Chun Liu; Chengfeng Li (Bulletin of Engineering Geology and the Environment, 2023)

Activation persulfate for efficient tetrabromobisphenol A degradation via carbon-based materials: Synergistic mechanism of doped N and Fe - Zhengfang Zhang; Yang Liu; Ying Zhang; Ruohan Li; Yuntao Guan (Journal of Hazardous Materials, 2023)

In vitro fermentation of heparin by the human gut microbiota: Changes in the microbiota community and metabolic functions - Chuan Zhang; Leilei Yu; Qixiao Zhai; Ruohan Zhao; Jianxin Zhao; Hao Zhang; Wei Chen; Fengwei Tian (Food Chemistry, 2023)

Recovery of nitrogen and phosphorus in wastewater by red mud-modified biochar and its potential application - Zhipeng Zhao; Bing Wang; Qianwei Feng; Miao Chen; Xueyang Zhang; Ruohan Zhao (Science of The Total Environment, 2023)

The F-box protein OsEBF2 confers the resistance to the brown planthopper (Nilparvata lugens Stål) - Feilong Ma; Zixin Li; Sayi Wang; Kejia Li; Fei Tang; Jingxuan Jia; Qiujin Zhao; Peihua Jing; Wenqing Yang; Congmin Hua; Haifu Han; Jiayin Xu; et al. (Plant Science, 2023)

Morphology and mass spectrometry-based chemical profiling of peltate glandular trichomes on Mentha haplocalyx Briq leaves - Ruohan Liu; Yutuan Wang; Conglian Liang; Zhijuan Zheng; Xiuwei Du; Zhanhu Cui; Yongqing Zhang; Hongyan Liu (Food Research International, 2023)

Subculture and Etiolation Treatment Promotes Rooting Ability of Upper Branches of Black Locust Crown - Jie Zhang; Ye Zhao; Anan Duan; Wei Wang; Yuhan Sun; Li Dong; Sen Cao; Xiuyu Li; Xiaodi Liu; Chao Han; Saleem Uddin; Wei Bi; et al. (Forest Science, 2023)
The black locust (Robinia pseudoacacia L.) is an economically and ecologically important tree worldwide. However, maturation and position effects affect its asexual reproduction. Despite etiolation treatment and successive subcultures promoting the plant cutting’s rooting rate, whether the promoting effects of aging (upper) branches and young (lower) branches are consistent is unknown. Therefore, we evaluated the relevant rooting ability indicators of tree age effect and its location effect in 26-year-old R. pseudoacacia trees and the current-year branches of different parts. Branches of the upper and lower parts of these trees underwent accelerated germination to generate shoots as explants. We subjected the tissue culture–generated shoots to an etiolation treatment to investigate how the treatment and subculture time affected the rooting ability of the shoot explants induced by different parts of the black locust branch. Tissue culture shoots subjected to the etiolation treatment exhibited a 2–3 day shorter rooting time. Shoots from the upper crown organs achieved a rejuvenation effect, which manifested as enhanced rooting capacity. Our study results provide a theoretical basis for maintaining the juvenility and consistency of clones. Besides having theoretical and practical value, our study also guides the selection of suitable propagation materials for production.

Sulfur-containing benzofurans and α-pyrones from the mangrove-derived fungus Talaromyces sp. WHUF0341 - Ruohan Zhang; Jinxin Zhang; Ruiyun Huo; Yaxin Xue; Kui Hong; Ling Liu (Frontiers in Marine Science, 2022)
Two new sulfur-containing benzofurans, talarobenzofurans A and B ( 1 and 2 ), one new benzofuran talarobenzofuran C ( 3 ) and two new α -pyrones talaropyrones A and B ( 5 and 6 ), along with five known compounds eurothiocin A ( 4 ), nodulisporipyrone A ( 7 ), peniazaphilin B ( 8 ), ramulosin ( 9 ) and 6-hydroxyramulosin ( 10 ) were isolated and identified from the culture extract of the mangrove-derived fungus Talaromyces sp. WHUF0341 guided by OSMAC (one strain-many compounds) strategy. Their structures were established by extensive spectroscopic data analysis, the modified Mosher’s method and electronic circular dichroism (ECD) calculations. Structurally, compounds 1 and 2 possesed the unique thioester moiety derived from benzofuran and 2-hydroxy-3-mercaptopropionic acid, which was rarely-observed in natural products. The α -glucosidase inhibitory and antibacterial activities of the isolated compounds were evaluated. Compounds 3 and 4 exhibited inhibitory effects against α -glucosidase activity with IC 50 values of 48.9 ± 2.16 and 8.8 ± 1.08 µM, respectively. The inhibitory type of 3 on α -glucosidase was determined as non-competitive-type inhibition with K i value of 242.3 μM by using Lineweaver-Burk double reciprocal and Dixon single reciprocal plots. Meanwhile, the binding model of 3 and 4 with α -glucosidase was determined by molecular docking assay. The biosynthetic pathways of compounds 1 − 4 were also proposed. This study suggested that benzofurans 3 and 4 could be potential lead compounds for the hypoglycemic drugs.

The effect of cylindrospermopsin on the bacterioplankton community: a microcosm experiment on water from Dishui Lake, Shanghai, China - Sicheng Yin; Ruohan Huang; Erik Jeppesen; Lijing Chen; Liqing Wang; Xin Fang; Wei Zhang (Journal of Oceanology and Limnology, 2022)

Correction to: Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2022)

Alterations in functional network centrality in first-episode drug-naïve adolescent-onset schizophrenia - Ming Zhou; Lihua Zhuo; Ruofei Ji; Yingxue Gao; Hongchao Yao; Ruohan Feng; Lianqing Zhang; Guoping Huang; Xiaoqi Huang (Brain Imaging and Behavior, 2022)

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Application of Metabolomics to the Discovery of Biomarkers for Ischemic Stroke in the Murine Model: a Comparison with the Clinical Results - Jinjing Jia; Hangyao Zhang; Xiaoyi Liang; Yuning Dai; Lihe Liu; Kaiwen Tan; Ruohan Ma; Jiahuan Luo; Yi Ding; Chaofu Ke (Molecular Neurobiology, 2021)

Estimating the shear wave velocity structure above the fresh bedrock based on small scale microtremor observation array - Baoqing Tian; Yanan Du; Huazhong Jiang; Ruohan Zhang; Jiangjie Zhang (Bulletin of Engineering Geology and the Environment, 2020)

miRNAs play essential roles in the floral thermogenesis of Magnolia denudata (Magnoliaceae) - Xiangyu Liu; Dechang Cao; Xiangyu Ji; Zhixiang Zhang; Yanwei Wang; Ruohan Wang (Trees, 2015)

Temperature regulation of floral buds and floral thermogenicity in Magnolia denudata (Magnoliaceae) - Ruohan Wang; Xiangyu Liu; Shulin Mou; Sai Xu; Zhixiang Zhang (Trees, 2013)